2000
DOI: 10.1002/(sici)1097-0061(20000115)16:1<35::aid-yea504>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae gene ISW2 encodes a microtubule‐interacting protein required for premeiotic DNA replication

Abstract: A molecular genetic characterization of the ORF YOR304W (ISW2), identi®ed in a screen of a yeast lgt11 library using a monoclonal antibody that reacts with a 210 kDa mammalian microtubule-interacting protein, is presented in this paper. The protein encoded by the ORF YOR304W is 50% identical to the Drosophila nucleosome remodelling factor ISWI and is therefore a new member of the SNF2 protein family and has been recently entered into SDG as ISW2. Although not essential for vegetative growth, we found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This complex, which is related to the Swi/Snf family of ATP-dependent chromatin-remodeling enzymes, represses genes by repositioning the promoter nucleosomes into transcriptionally inactive chromatin (Kent et al, 2001;Langst and Becker, 2001). The Isw2p complex contributes to repression of IME2 and other early meiotic genes during growth and also to their induction under sporulation conditions and hence is required for meiotic initiation (Trachtulcova et al, 2000). Thus, the Isw2p complex, Rpd3p complex, and Gcn5p complex may coordinately regulate many early meiotic genes through a concerted switch in the chromatin structure of these promoters.…”
Section: The Targets Of Nutritional Regulation Of Meiotic Initiationmentioning
confidence: 99%
“…This complex, which is related to the Swi/Snf family of ATP-dependent chromatin-remodeling enzymes, represses genes by repositioning the promoter nucleosomes into transcriptionally inactive chromatin (Kent et al, 2001;Langst and Becker, 2001). The Isw2p complex contributes to repression of IME2 and other early meiotic genes during growth and also to their induction under sporulation conditions and hence is required for meiotic initiation (Trachtulcova et al, 2000). Thus, the Isw2p complex, Rpd3p complex, and Gcn5p complex may coordinately regulate many early meiotic genes through a concerted switch in the chromatin structure of these promoters.…”
Section: The Targets Of Nutritional Regulation Of Meiotic Initiationmentioning
confidence: 99%
“…Cold Spring Harbor Laboratory Press on May 9, 2018 -Published by genesdev.cshlp.org Downloaded from It has been shown previously that diploid isw2 yeast are unable to undergo meiosis (Trachtulkova et al 2000), and recent work has confirmed that Isw2p functions to regulate early meiotic genes (Goldmark et al 2000). Meiosis in yeast is a response to starvation.…”
Section: Genes and Development 623mentioning
confidence: 99%
“…The Isw2-Itc1p complex was subsequently shown to be involved in the repression of other genes related to the starvation response, such as INO1 (Sugiyama & Nikawa, 2001) and PHO3 (Kent et al, 2001). The ISW2 gene encodes a yeast homologue of the Drosophila ISWI chromatin-remodelling ATPase (Tsukiyama et al, 1999;Trachtulcova et al, 2000), which is essential for development as well as for cell viability (Deuring et al, 2000). Members of this class of remodelling factors have been found so far in yeasts, Drosophila, Xenopus and human (Goldmark et al, 2000), and play key roles in modulating transcription through the regulation of chromatin structure.…”
Section: Introductionmentioning
confidence: 99%